2016
DOI: 10.1080/0284186x.2016.1223342
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for magnetic resonance imaging-guided salvage radiotherapy for prostate cancer

Abstract: MRI detects loco-regional disease in a substantial subset of patients with a biochemical recurrence after prostatectomy, especially in a PSA above 0.5 μg/l. Lack of MRI-based dose escalation on these macroscopic recurrences could explain some of the biochemical progression observed after SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Likewise, in the RT-treatment planning, MRI protocols combining T2weighted imaging, dynamic contrast-enhanced imaging and diffusion-weighted imaging are very useful for accurate TV contouring. Data confirming that MRI should be used for appropriate TV delineation comes from the European Organisation for Research and Treatment of Cancer (EORTC) guidelines and also from a recent analysis where 25% of local recurrences were located outside the postoperative CTV [23]. Indeed, recent data show MRI is able to detect loco-regional disease in patients with BCR with a PSA level of >0.5 ng/mL [24].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, in the RT-treatment planning, MRI protocols combining T2weighted imaging, dynamic contrast-enhanced imaging and diffusion-weighted imaging are very useful for accurate TV contouring. Data confirming that MRI should be used for appropriate TV delineation comes from the European Organisation for Research and Treatment of Cancer (EORTC) guidelines and also from a recent analysis where 25% of local recurrences were located outside the postoperative CTV [23]. Indeed, recent data show MRI is able to detect loco-regional disease in patients with BCR with a PSA level of >0.5 ng/mL [24].…”
Section: Discussionmentioning
confidence: 96%
“…The use of pelvic MRI to better target or boost radiotherapy fields in the setting of BCR is appealing (18,19). However, few data on the detection rate for or the utility of pelvic MRI in the setting of BCR at PSA levels at which men are still curable have been published (20)(21)(22). A retrospective review of 473 men who underwent pelvic MRI before SRT for BCR found that up to 57% of men had positive MRI results, 49% of recurrences were local, and 8% of recurrences were distant to the fossa (21).…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with a biochemical failure after RP undergo re-staging to rule out systemic disease before sRT [ 13 ], it would be desirable to have a diagnostic test that also addresses the presence of local disease. The identification along with the precise localisation of the disease within the prostatic fossa is supported by both the European Society Urologic Oncology and the American College of Radiology [ 14 , 15 ] since it may have prognostic value [ 16 , 17 ] and it may also optimise both sRT dose prescription and planning [ 18 , 19 ], although the role of a MR-directed boost to macroscopic disease remains undetermined.…”
Section: Discussionmentioning
confidence: 99%